The destruction of cultural property as a weapon of war: ISIS in Syria and Iraq - Turku, Helga (Palgrave Macmillan, 2018)
“This book aims to advance the understanding of cultural property and its significance in the overall strategy for anti-terrorism and peace building. As the author argues, ISIS’ orchestrated destruction and theft of cultural property has become a tactic of war. Through a historical and legal analysis, this book highlights new features in the pathology of a radical group’s behavior toward cultural objects as part of their horror campaign. Using constructivist ideas, it explains the importance of cultural property in the context of short-term and long-term security and analyses the evolution of laws and policies to protect it.” (Publisher's description)